2021
DOI: 10.18311/jfds/12/1/2020.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dentures on Palatal Rugae: An Investigation

Abstract: Aims: The aim of this study is to evaluate the rugae pattern changes (rugae number, length, shape, direction, and unification) in completely edentulous patients treated with complete denture. Materials and Methods: A total of 100 subjects were selected for the study. The experimental group comprised 60 participants (30 males and 30 females) who had undergone complete denture treatment and the control group comprised 40 participants (20 males and 20 females) who were dentulous and patients with fixed partial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous literature has demonstrated that palatal dimensions, arch depth, morphology, incisive papilla size, and palatal rugae could be indicative of sexual dimorphism in serving as sex predictors (gender-specific) [ 36 , 37 , 38 ]. In Negishi et al’s study, a moderate to high genetic contribution was found to influence palatal morphology, with the posterior palate having a greater genetic contribution to height than the anterior [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature has demonstrated that palatal dimensions, arch depth, morphology, incisive papilla size, and palatal rugae could be indicative of sexual dimorphism in serving as sex predictors (gender-specific) [ 36 , 37 , 38 ]. In Negishi et al’s study, a moderate to high genetic contribution was found to influence palatal morphology, with the posterior palate having a greater genetic contribution to height than the anterior [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged use of complete dentures imparts pressure and compression on palatal mucosa, causing histological changes in palatal rugae [ 96 , 97 ]. This in turn changes the length of rugae but does not affect their number and orientation [ 36 , 98 ].…”
Section: Discussionmentioning
confidence: 99%